2012
DOI: 10.2169/internalmedicine.51.6919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Simple Aspiration Therapy in the Initial Treatment for Primary Spontaneous Pneumothorax

Abstract: Objective A retrospective evaluation of the effectiveness of simple aspiration therapy in primary spontaneous pneumothorax was carried out. Methods We enrolled 143 patients with mild and moderate primary spontaneous pneumothorax between June 2006 and October 2010. Clinical backgrounds and therapeutic results from 92 patients that underwent simple aspiration therapy were assessed. Results All patients were treated safely without any serious complications. With the exception of one patient with an unknown result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This was in agreement with the Australian guidelines (44). Furthermore, Nishiuma and his colleagues (45) held the view that needle aspiration should be considered as the first choice in the management of mild and moderate PSP ("mild" was defined as the pneumothorax cranial to the level of collarbone area; "moderate" referred to intermediate between mild and severe pneumothorax; and "severe" was defined as the pneumothorax with completely collapsed lung), opposite to the view of Kuester (46). Low success rate of needle aspiration was the shortcoming pointed out most frequently.…”
Section: Discussionsupporting
confidence: 87%
“…This was in agreement with the Australian guidelines (44). Furthermore, Nishiuma and his colleagues (45) held the view that needle aspiration should be considered as the first choice in the management of mild and moderate PSP ("mild" was defined as the pneumothorax cranial to the level of collarbone area; "moderate" referred to intermediate between mild and severe pneumothorax; and "severe" was defined as the pneumothorax with completely collapsed lung), opposite to the view of Kuester (46). Low success rate of needle aspiration was the shortcoming pointed out most frequently.…”
Section: Discussionsupporting
confidence: 87%
“…Clinical study AL-ALAWI [17] AL-MOURGI [18] ANDERSEN [19] CASALI [10] CHAN [12] CHEN [20] CHEN [21] CHEN [22] GANESALINGAM [9] HARVEY [23] KARASAKI [25] KIM [26] KUAN [27] LICHTER [28] LIGHT [29] MARTÍNEZ-RAMOS [30] MEHTA [31] NISHIUMA [32] NOH [33] NOH [34] OLESEN [6] OUANES-BESBES [13] PRIMAVESI [8] SADIKOT [ due to nutritional deficiencies affecting α 1 -antitrypsin levels or due to unbalanced physical development, was supported by two papers [5,6,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Invasive treatment is usually required as initial management when a PTX is large or accompanied by significant symptoms. Although ITD has been preferred as the standard invasive therapy, recent studies have reported that aspiration and catheterization connected to a one-way valve were also effective for re-expanding a collapsed lung and had similar recurrence rates [68]. …”
Section: Introductionmentioning
confidence: 99%